What is the fate of scientific abstracts? The publication rates of abstracts presented at the 7th National Congress of Gynecology and Obstetrics - (:unkn) unknown (GALENOS YAYINCILIK, 2015)
Objective: Oral and poster presentations held at national and international congresses are recognized as valuable tools for sharing current scientific data and experience among physicians. However, a large proportion of these works fail to be published in scientific journals. We have designed a study to identify the publication rate of presentations held at the 7th National Congress of Obstetrics and Gynecology in 2009. Materials and Methods: A systematic search of databases was performed using author names and key words from the abstract title to locate publications in peer-reviewed journals corresponding to the presentations held at the 7th National Congress of Obstetrics and Gynecology. Information regarding mode of presentation, topic, type of affiliation, name and impact factor of the scientific journal, change in author names and time elapsed between presentation and publication were recorded and analyzed statistically. Results: Of 243 abstracts that were presented at the congress, 45 papers (18.5%) were published in international peer-reviewed journals, whereas 39 (16%) were published in national journals. The mean time to publication was 17 +/- 2 months for international and 11 +/- 4 months for national journals (p=0.102). The international publication rate of oral presentations was significantly higher than that of poster presentations (50% vs. 16.2%; p<0.03). The manuscripts were published in a total of 21 journals, with four journals accounting for 49% of the publications. The comparison of the publication rates of the universities with other institutions has yielded no significant difference. Conclusion: Alltough a significant proportion of the abstracts presented in the 7th National Gynecology and Obstetrics Congress have been succesfully converted to publication overall, only a limited percentage of all abstracts have been published in international peer-reviewed journals. The relatively higher conversion to international publication rate of the oral presentations show that they are of higher interest and clinical relevance.
Keywords: Meeting abstracts; congresses; manuscripts; unpublished works